55.3k views
1 vote
Solve the equation below. Show all steps for full points.

7r + 13 = 7 + 6r

User Samran
by
5.4k points

2 Answers

5 votes

Answer:


\boxed{r=-6}

Explanation:


All~you~have~to~do~is~collect ~the ~constants~ on ~one ~side ~of ~the~ =~ and
the~variables~(including~terms~with~r)~ on ~the~ other~ side.~ Then,
manipulate~it,~ so~ that~ you~ only~ have~ a ~single ~r~on~ its~ own~ on~ one~ side
and ~everything~ else~ on~ the ~other.

Applying the method :


Subtract ~6r~from~ both ~sides:


6r-6r+7~~=~~13+7r-6r


0+7~~=~~13+r


Subtract~13~from~both~sides:


7-13~~=~~13-13+r


-6~~=~~0+r


r=-6

The short cut approach for add or subtract is:


Move~ something~ to~ the~ other ~side ~of~ the~ ``=

User Jeguyer
by
6.2k points
2 votes

Answer:

r = - 6

Explanation:

Given

7r + 13 = 7 + 6r ( subtract 6r from both sides )

r + 13 = 7 ( subtract 13 from both sides )

r = - 6

User Wyx
by
5.6k points